The sources of self-efficacy in experienced and competitive endurance athletes - Anstiss, P. A.; Meijen, C.; Marcora, S. M. (International Journal of Sport and Exercise Psychology, 2020)
Endurance athletes draw on several sources of self-efficacy, but there is a limited understanding of what information within these sources specifically contributes towards self-efficacy. An increased understanding and awareness of the sources of self-efficacy for endurance performance would allow the design and delivery of more effective self-efficacy interventions. The aim of the current study was to identify sources of self-efficacy specific to the endurance sport domain. Semi-structured interviews were conducted with twelve experienced competitive endurance athletes who had been competing in their endurance sport for an average of 12.2 ± 6.25 years. Interviews were recorded, transcribed verbatim, and analysed using deductive thematic analysis. Past performance experiences, physiological states, social/verbal persuasions and emotional states were generated as initial themes. Within these themes, six sub-themes were identified: cumulative experiences, challenge and adversity, physical familiarity, social support, self-talk, and doubt and worry. Our results indicate that endurance athletes make use of several sources of self-efficacy in the formation and maintenance of their self-efficacy beliefs. Specifically, the culmination of experiences, experiences of overcoming challenge and adversity, and a sense of physical familiarity appeared to key sources in the endurance sport domain.